Psychosocial stress and bacterial vaginosis in adult women - Ova Emilia Ova Emilia (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Objectlve:The purpose of this study was to assess the association of bacterial vaginosis with psychosocial stress with in adult women.Methods: A cross sectional design was used. Adult women (n = 320) aged 15 to 44 years were recruited at routine health care visits. Assessments were conducted on clinical symptoms, and an extensive selfreport interview.Results: Psychosocial stress was associated with overall prevalence of bacterial vaginosis (ratio prevalence, 1.22; 95% CI, 1.13-1.34). Factors that may influence the association were age, frequency of douching, frequency of vaginal intercourse and use of hormonal contraceptive. The association was not changed appreciably by the control for behavioral and demographic characteristics.Conclusion: Increased psychosocial stress is associated with greater bacterial vaginosis prevalence independent of other risk factors.Key words: bacterial vaginosis - stress - immune functioning